2016
DOI: 10.1016/j.brs.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Brain Stimulation Increases Ability to Resist Smoking

Abstract: Background The ability to exert self-control over temptation is a fundamental component of smoking behavior change. Transcranial direct current stimulation (tDCS) of the dorsolateral prefrontal cortex (DLPFC) has been shown to modulate cognitive control circuits. Although prior studies show that stimulation reduces cigarette craving and self-reported smoking, effects on ability to resist smoking have not been investigated directly. Objectives We assessed effects of a single 20-minute session of 1.0 mA anodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 45 publications
2
54
2
Order By: Relevance
“…Eight studies have examined the effects of tDCS on nicotine craving in dependent participants. All studies applied 2.0 mA stimulation for 15–30 minutes, except one by Falcone et al, who used a stimulation intensity of 1.0 mA for 20 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies have examined the effects of tDCS on nicotine craving in dependent participants. All studies applied 2.0 mA stimulation for 15–30 minutes, except one by Falcone et al, who used a stimulation intensity of 1.0 mA for 20 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies have examined the effects of tDCS on nicotine craving in dependent participants. All studies applied 2.0 mA stimulation for 15–30 minutes, except one by Falcone et al, who used a stimulation intensity of 1.0 mA for 20 minutes. Five of the aforementioned studies demonstrated positive effects on nicotine cravings and/or consumption, with significant reductions seen across participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Falcone et al (2016) investigated the effect of a single 20-min session of 1.0 mA anodal stimulation over the left DLPFC on 25 smokers. They found that the stimulation could improve their ability to resist smoking.…”
Section: Tdcs Applications In Clinical Samplesmentioning
confidence: 99%
“…The precise mechanisms by which tDCS works are currently unclear, although there are some data that suggest anodal tDCS increases synchrony of neuronal firing as a result of reduced GABA (Kim et al., ) and increased glutamate activity (Clark et al., ). Prior research has shown that application of anodal tDCS over dorsolateral prefrontal cortex (DLPFC) reduces craving for alcohol (Boggio et al., ; Klauss et al., ), cigarettes (Boggio et al., ; Falcone et al., ), marijuana (Boggio et al., ), and food (Fregni et al., ). A recent treatment trial in which anodal tDCS was applied over right DLPFC (with cathode placed on left DLPFC) in alcohol‐dependent patients in a series of 10 sessions showed reduced craving and increased 3‐month abstinence in the verum tDCS group compared to the sham group (Klauss et al., ).…”
mentioning
confidence: 99%